Investigation of physics-mechanical properties of entrails in Antarctic in Argentine islands region - V. Zhukovskiy; A. Gokhman; E. Karyagin (Ukrainian Antarctic Journal, 2012)
In the Academic Vernadscy station by monitoring of seismic events at the 2008-2009 years the data of the seismic waves velocities distribution according to orientation, internal stresses and Yong’s modulus over the depth distributions were obtained.  It is suggested to use Yung’s modulus as a controllable value that characterizes stress-deformed state of the medium under investigation.